2018
DOI: 10.1007/s00261-018-1528-x
|View full text |Cite
|
Sign up to set email alerts
|

Using T1 mapping in cardiovascular magnetic resonance to assess congestive hepatopathy

Abstract: The goal of this study was to assess the ability of quantitative T1 cardiovascular magnetic resonance (CMR) imaging to calculate liver extracellular volume (ECV) in patients with varying degrees of congestive hepatopathy (CH). T1 measurements and ECV calculations were performed retrospectively in three cohorts of patients: normal cardiac function, tetralogy of fallot (TOF) repair and Fontan palliation. All CMR studies included modified look-locker inversion recovery (MOLLI) T1 mapping scans performed pre- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
4
11
1
Order By: Relevance
“…Only pilot data in 16 adult Fontan patients yielded CMR T1 and ECV levels comparable to our cohort [14]. In our study, Fontan patients demonstrated elevated native T1 times, in line with results from USE, computed tomography and postmortem studies which have indicated increased stiffness and evidence of fibrosis [3134].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Only pilot data in 16 adult Fontan patients yielded CMR T1 and ECV levels comparable to our cohort [14]. In our study, Fontan patients demonstrated elevated native T1 times, in line with results from USE, computed tomography and postmortem studies which have indicated increased stiffness and evidence of fibrosis [3134].…”
Section: Discussionsupporting
confidence: 87%
“…All ROIs were traced to avoid major vessels, the gall bladder and hepatic surface (Fig. 1) [13, 14]. For blood pool T1 measurements, ROIs were placed in the cardiac lumen and in a hepatic vein as close as possible to the diaphragm, while avoiding myocardial trabeculations and hepatic tissue, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The elevated hepatic T1, extracellular volume fraction, and elastography values confirmed previous findings from retrospective MR studies in adults and children with Fontan [18,21,22] and studies on US and MR elastography after Fontan completion [19,20,27,28]. The advantage of our study was the representative, unselected, relatively large national cohort of adolescents with Fontan circulation.…”
Section: Discussionsupporting
confidence: 87%
“…US shear-wave elastography is simpler and less resource-demanding than MR, and is routinely used to assess adult chronic liver disease [16,17]. Few studies have employed hepatic MR T1 mapping or elastography to evaluate fibrosis or congestion in people with Fontan circulation [18][19][20][21][22]. We hypothesized that adolescents with Fontan circulation might display elevations in fibrosis markers, based on MR T1 mapping, extracellular volume fraction, and US shear-wave elastography.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used and widely available myocardial T 1 -mapping methods based on balanced steady-state free-precession (bSSFP) acquisitions, such as modified Look-Locker inversion recovery (MOLLI) 12 or shortened MOLLI (ShMOLLI), 13 are increasingly used for T 1 mapping in the liver. 2,[14][15][16][17] Unfortunately, these methods have large and complex T 1 errors when applied to mixed water-fat systems. 16,18 A fat-correction approach for the ShMOLLI T 1 mapping method has been illustrated, but requires additional acquisitions to assess off-resonance frequency and fat content, in combination with numerical simulations.…”
Section: Introductionmentioning
confidence: 99%